Modeling the impact of residential HVAC filtration on indoor particles of outdoor origin (RP-1691). (18th May 2016) - Azimi, Parham; Zhao, Dan; Stephens, Brent
Abstract : Much of human exposure to airborne particles of outdoor origin, including fine particles smaller than 2.5 μm (PM2.5 ) and ultrafine particles smaller than 0.1 μm (UFPs), occurs in residences. High-efficiency central HVAC filters are increasingly being used in residences, but questions remain about their effectiveness in reducing indoor PM2.5 and UFPs of outdoor origin in homes operating under realistic conditions (e.g., with HVAC systems operating only to meet heating or cooling demands). Here dynamic building energy and indoor air mass balance modeling are combined to estimate the impacts of 11 HVAC filters (minimum efficiency reporting value [MERV] 5 through high-efficiency particulate air [HEPA]) on indoor concentrations of PM2.5 and UFPs of outdoor origin in multiple vintages of prototypical single-family residences relying on either infiltration or mechanical ventilation systems in 22 U.S. cities. Results demonstrate that higher-efficiency HVAC filters can meaningfully reduce indoor proportions of outdoor PM2.5 and UFPs inside residences, but home vintage, climate zone, and ventilation strategy strongly influence the outcomes due to widely varying air exchange rates, HVAC system runtimes, and sources of ventilation air. Higher efficiency filters had a greater impact in older, leakier homes relying on infiltration alone and in new homes relying on supply-only mechanical ventilation systems designed to meet ASHRAE Standard 62.2.